Active-site molecular docking of nigellidine with nucleocapsid–NSP2–MPro of COVID-19 and to human IL1R–IL6R and strong antioxidant role of Nigella sativa in experimental rats. (28th May 2022) - Maiti, Smarajit; Banerjee, Amrita; Nazmeen, Aarifa; Kanwar, Mehak; Das, Shilpa
Abstract: The recent outbreak of SARS CoV-2 has changed the global scenario of human lives/economy. A significant number of the non-survivors showed cardiac renal vasculature dysfunction. A 'cytokine storm' namely, interleukin IL6–IL1 receptors, i.e. IL6R–IL1R over-functioning was reported. Here, nigellidine, an indazole alkaloid and key component of Nigella sativa L . (NS) commonly known as black cumin seed was analysed for COVID-19 protein targeting and IL1R–IL6R inhibition through molecular docking study and biochemical study in experimental rat to evaluate antioxidative capacity. The NMR/X-ray crystallographic/electron microscopic structures of COVID-19 main protease (6LU7)/spike glycoprotein (6vsb)/NSP2 (QHD43415_2)/nucleocapsid (QHD43423), human IL1R (1itb)-IL6R (1pm9) from PDB were retrieved analysed for receptor–ligand interaction. Then, those structures were docked with nigellidine using AutoDock and PatchDock server. A brief comparison was made with nigellicine thymoquinone from N. sativa. Where nigellidine showed highest binding energy of −6.6 kcal/mol, ligand efficiency of −0.3 with COVID19 Nsp2 forming bonds with amino acid CYS240 present in binding pocket. Nigellidine showed strong interaction with main protease (BE: –6.38/LE: –0.29). Nigellidine showed affinity to IL1R (–6.23). The NS treated rat showed marked decline in ALP-SGPT-SGOT-malondialdehyde (MDA) than the basal levels. From the Western blot and activity analysis, it was observed that Nigellidine (sulphuryl group drug) showed no impact on phenol-catalysing ASTIV and steroid-catalysing oestrogen-sulphotransferase expressions and activities in liver tissue and thus has no influence in sulphation-mediated adverse metabolic processes. Conclusively, nigellidine has hepato-reno-protective/antioxidant-immunomodulatory/anti-inflammatory activities with inhibit potentials of COVID-19 proteins. Further validation is necessary.